Correlation of Colony Lactobacillus spp. with The Incident of Overactive Bladder with OBSS Score at Pauh Primary Health Center Padang - Rimbun Wahyu Gumilar; Bobby Indra Utama; Hafni Bachtiar (Andalas Obstetrics And Gynecology Journal, 2021)
Background : Overactive bladder (OAB) is a group of urgent symptoms, with or without urgent incontinence. Research shows that some Lactobacillus spp. can be a sign of a women bladder’s good health; and found a decrease number of Lactobacillus spp. in patients with OAB. This study aims to assess the correlation of Lactobacillus spp. colony with OAB using the OABSS score at Pauh Primary Health Center, Padang.Method : This research is an analytic study with a cross sectional comparative design. The research was conducted from December 2019 to February 2020 at Pauh Primary Health Center. All women aged 20-40 years who came to Pauh Primary Health Center during the study period were included in the study. Pregnant women, having pelvic abnormalities and a history of other urinary tract diseases or having a history of hypertension and diabetes mellitus were excluded in the study. Numerical data are presented in the form of central tendency. Bivariate analysis was performed using the t-independent test if the data distribution was normal and the Kolmogorov-Smirnov test if the distribution of the data was not normally distributed.Result: There were 42 samples consisting of 21 OAB respondents and 21 normal respondents. The age of the respondents in the OAB group was 28 ± 6.8 years, while the normal group was 32 ± 7.3 years (p> 0.05). The number of Lactobacillus spp colonies in the normal group was higher than the OAB group, namely 16,389,670 ± 74,380,427.9 CU / ml compared to 15,229,634 ± 67,553,932.9 CU / ml (p> 0.05).Conclusion: There was no correlation between the number of Lactobacillus Spp colonies and the incidence of Overactive Bladder. It is necessary to do further research regarding other risk factors associated with the incidence of OAB and the causes of the decrease number of Lactobacillus spp colonies in OAB patients and the presence of other microorganisms, especially pathogenic microorganisms. Keywords: overactive bladder, Lactobacillus, OABSS score